4‐OH‐TEMPO/TCQ/TBN/HCl: A Metal‐Free Catalytic System for Aerobic Oxidation of Alcohols under Mild Conditions. Issue 9 (12th August 2015) - Dong, Yanli; Zhao, Xiaomei; Liu, Renhua
Abstract A green and economical catalyst system, 4‐OH‐TEMPO/TCQ/TBN/HCl, for the aerobic oxidation of a broad range of primary and secondary alcohols to the corresponding carbonyl compounds has been developed. These reactions proceed without transition‐metals under mild conditions with excellent yields.